Lipid raft proteomics identify endothelial myosin-9 (MYH9) as a regulator of low-density lipoprotein transcytosis and atherosclerosis - Erika Jang; Siavash Ghaffari; Andria Henry; Grace Wen; Tse Wing Winnie Ho; Wan Hei Cheng; Yunfan Lyu; Kuiru Wei; Changsen Wang; Casey E. Romanoski; Ying Wang; Myron I. Cybulsky; et al. (Proceedings of the National Academy of Sciences, 2025)
Background: In early atherosclerosis, circulating Low-Density Lipoprotein (LDL) crosses the endothelium by transcytosis. This involves caveolar uptake of LDL by scavenger receptor BI (SR-BI) and activin-like kinase 1 (ALK1) and requires the protein caveolin-1 (Cav-1). We identified mediators of LDL transcytosis by isolating membrane microdomains enriched in caveolin-1 from human coronary endothelial cells (HCAECs) treated with LDL and performing mass spectrometry. One of the proteins identified was myosin-9 (MYH9). Methods: Total internal reflection fluorescence microscopy was conducted to measure LDL transcytosis by HCAECs. We measured LDL transcytosis in vivo in mice lacking endothelial MYH9 (EC- Myh9 −/− ). Atherosclerosis studies were also performed in EC- Myh9 −/− deleted of hepatic LDLR via (adeno-associated virus, AAV)-CRISPR. Additionally, we performed analysis of human transcriptomic data. Results: Gene ontology analysis in human aortic endothelial cells suggested a role for MYH9 in exocytosis. Both knockdown and pharmacologic inhibition of MYH9 inhibited LDL transcytosis. MYH9 depletion caused an accumulation of LDL-containing vesicles at the base of the cell; overexpression caused an increase in LDL exocytosis. EC- Myh9 −/− mice accumulated less LDL in the aortic arch after acute injection with LDL. To investigate the role of MYH9 in atherosclerosis, we deleted hepatic LDL in EC- Myh9 −/− mice using AAV-CRISPR and fed them a high-fat diet. The aortic arch and root of AAV-CRISPR; EC- Myh9 −/− mice exhibited smaller plaques. Human transcriptomic data showed greater messenger RNA (mRNA) levels of aortic MYH9 in atherosclerotic aortas compared to healthy controls. Conclusions: Lipid raft proteomics identified MYH9 as a regulator of LDL transcytosis. MYH9 is required for endothelial LDL exocytosis and contributes to early atherosclerosis.